The Role of Teachers’ Cultural Competence in Enhancing Student Engagement in English Language Learning - Siti Nor Elisa; Abdul Halim; Khusnul Khatimah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Teaching English in a multicultural classroom requires teachers to have cultural competence in order to create an inclusive learning environment and encourage student engagement. This study aims to analyze the impact of teachers' cultural competence on student engagement in the English language learning process in culturally diverse EFL classrooms. This study employs a mixed-methods approach, examining not only the relationship between cultural competence and student participation but also the strategies implemented and challenges faced by teachers with cultural competence. Data collection was conducted through student questionnaires (pre-test and post-test) to measure engagement, semi-structured interviews with EFL teachers, and classroom observations. Quantitative data were analyzed using SPSS for descriptive and inferential statistics, while qualitative data were analyzed thematically. The results of the study indicate that teachers' ability to incorporate students' cultural backgrounds into the learning process can significantly enhance students' motivation, activity, and learning outcomes. This study contributes to the development of inclusive teaching practices in language learning environments rich in cultural diversity.